Analisis Perkawinan Beda Agama Perspektif KHI, HAM dan CLD-KHI - Rizqon, Rizqon (Fakultas Syariah INSURI Ponorogo, 2022)
Marriage is the right of every individual that should not be discriminated against. Nowadays, the issue of interfaith marriage often reaps a lot of debate, especially regarding its prohibition which is considered to discriminate against rights, as well as regarding its permissibility which is considered to be contrary to the constitution and religious norms. The purpose of this study was to analyze interfaith marriages from the perspective of KHI, HAM and CLD-KHI. This research is a library research type. The approach used is a normative approach, which aims to analyze interfaith marriages from a legal perspective, namely KHI, HAM and CLD-KHI. The data contained in the research was collected using the Documentation technique, then analyzed using the Content Analysis technique. From the results of this study it was found that the freedom to build a household in human rights has a relationship with the Marriage Law in force in Indonesia. Human rights only guarantee the freedom and protection of individual rights to marry, while their legal status still refers to the Marriage Law and the Marriage Law. KHI through its articles has strictly prohibited interfaith marriage, because according to KHI marriage is only valid if it is carried out by two people who have the same belief or religion. The CLD-KHI as a counter text to the KHI allows the practice of interfaith marriages on the grounds of upholding the principles of pluralism, nationalism, democracy, and human rights. This permissibility denies the articles in the KHI such as the prohibition, prevention, and annulment of marriages due to different religions. The conclusion is that interfaith marriages are normatively strictly prohibited in Indonesia. His abilities based on the principles of pluralism, democracy or human rights cannot be applied in Indonesia, where normatively the marriage law refers to religious law